Ag quantum dots promoted Li4Ti5O12/TiO2 nanosheets with ultrahigh reversible capacity and super rate performance for power lithium-ion batteries. Issue 43 (25th October 2016) - Ge, Hao; Cui, Luxia; Zhang, Bing; Ma, Tian-Yi; Song, Xi-Ming
Abstract : Rationally designed Ag quantum dot modified Li4 Ti5 O12 /TiO2 nanosheets demonstrate ultrahigh reversible capability and super rate performance for lithium-ion batteries. Abstract : Spinel Li4 Ti5 O12 (LTO) has been widely studied as a promising anode material due to its outstanding structural stability and remarkable safety. However, the poor electron conductivity and low lithium-ion diffusion coefficient seriously limit its rate capability for the application in power lithium-ion batteries (LIBs). Herein, we demonstrate rationally designed Ag quantum dot (QD) modified LTO/TiO2 nanosheets (Ag-LTO/TiO2 NSs) synthesized via a facile hydrothermal process followed by heat treatment, highlighting simultaneously the promotion of electron conductivity and lithium-ion diffusion coefficient. The newly prepared Ag-LTO/TiO2 NSs deliver an ultrahigh reversible capacity of 177 mA h g −1 at 0.5C and a superior rate performance of more than 148 mA h g −1 at 30C between 1.0 and 2.5 V. The achieved superior electrochemical performance largely surpasses that of the state-of-the-art LTO-based materials for LIBs. The present work provides a facile yet effective approach to significantly boost the high rate capability of LTO/TiO2 composites. These novel quantum dot modified 2-dimensional (2D) materials will pave the way to a new family of carbon-free anode materials in response to the increasing demands for high-power energy storage.